WHY YOU SHOULD NOT SUBMIT YOUR WORK TO MORE THAN ONE JOURNAL AT A TIME - Wager, Liz (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
All researchers should seek to publish their work in peer-reviewed journals, but to publish it more than once (without a special reason and clear cross-referencing) is not acceptable.